PENGARUH PREFERENSI RESIKO, LITERASI EKONOMI, PENGETAHUAN GALERI INVESTASI TERHADAP MINAT INVESTASI MAHASISWA FAKULTAS EKONOMIKA DAN BISNIS - Rine Gesta; Endah Andayani; Auliana Farrabanie Al Arsy (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2019)
This study aims to determine the effect of Risk Preference, Economic literacy and Investment Gallery on the investment interests of Economics and Business Faculty students. (This type of research uses quantitative research methods using multiple linear regression. The population in this study were students of the 2015 Kanjuruhan Malang Faculty of Economics and Business, amounting to 412 people. with a research sample of 25% of the population of 103 students. The data obtained was analyzed with the help of SPSS version 22.00 for Windows. Based on the calculation results, it is known that: (1) There is an influence of Risk Preference, Economic literacy and Investment Gallery on the investment interest of Economics and Business Faculty students. (2) There is no Risk Preference Effect on investment interest in Economics and Business Faculty students. (3) There is an Influence of Economic Literacy on the investment interest of the Economics and Business Faculty students (4) There is an Investment Gallery Effect on the investment interest of the Economics and Business Faculty students. The results of multiple linear regression analysis showed that the F value of 24.771 with a significance level of 0.000 <0.05, it can be said that Risk Preference (X1), Economic Literacy (X2), and Knowledge of Investment Gallery (X3) have simultaneous or joint effects. equal to Investment Interest (Y).